1985
DOI: 10.1136/gut.26.8.816
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the small intestinal mucosa in young, adult, and old rats submitted to protein deficiency and rehabilitation.

Abstract: SUMMARY Linear and stereological morphometric methods were applied to the jejunal and ileal mucosa of young, adult, and old male Wistar rats submitted to protein deficiency and rehabilitation. The animals were fed ad libitum a 2% casein diet during 42 days and then received a 20% casein diet for 30 days. Food intake, body weights, and plasma protein concentrations were recorded. In the young protein deficient rats values of mucosal height, surface area, and volume of the lamina propria were significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
3
13
1
Order By: Relevance
“…The mucosa thickness decreased in G3 animals compared to G1 animals (p<0.05), which has also been observed in other studies (Viteri and Schneider 1974, Rodrigues et al 1985, Da CostaRibeiro et al 1987, Torrejais et al 1995, Natali et al 2000, Schoffen et al 2005, De Azevedo et al 2007, Hermes et al 2008. Conversely, the mucosa was less reduced in G4 (7.4%) than in G3 (13.5%) compared to well-nourished G1 animals (p<0.05), as illustrated in Figure 2.…”
Section: Probiotics Protect the Jejunum Of Malnourished Ratsupporting
confidence: 70%
See 1 more Smart Citation
“…The mucosa thickness decreased in G3 animals compared to G1 animals (p<0.05), which has also been observed in other studies (Viteri and Schneider 1974, Rodrigues et al 1985, Da CostaRibeiro et al 1987, Torrejais et al 1995, Natali et al 2000, Schoffen et al 2005, De Azevedo et al 2007, Hermes et al 2008. Conversely, the mucosa was less reduced in G4 (7.4%) than in G3 (13.5%) compared to well-nourished G1 animals (p<0.05), as illustrated in Figure 2.…”
Section: Probiotics Protect the Jejunum Of Malnourished Ratsupporting
confidence: 70%
“…The morphological alterations induced by malnutrition have been thoroughly investigated. Studies using experimental proteinmalnutrition models have shown a decreased thickness of bowel wall layers, such as reductions of the mucosa (Rodrigues et al 1985, Firmansyah et al 1989, Torrejais et al 1995, Natali et al 2000, Brandão et al 2003, Gurmini et al 2005, Schoffen et al 2005, De Azevedo et al 2007, Hermes et al 2008, enterocyte height (Brandão et al 2003, De Azevedo et al 2007, Hermes et al 2008, villi height (Firmansyah et al 1989, Natali et al 2000, Gurmini et al 2005, crypt depth (Firmansyah et al 1989, Hermes et al 2008, and muscular layer thickness (Torrejais et al 1995, Natali et al 2000, Brandão et al 2003, De Azevedo et al 2007). Therefore, strategies to correct or reduce the damage caused by malnutrition must be investigated.…”
mentioning
confidence: 99%
“…1984;Dollet et al, 1985;Rodrigues et al, 1985;Nwankwo et al, 1985;Swenne et al, 1987], Several causes might explain the discrepancies, such as the difference in food composition or period of time that the diet was applied. The need in protein is obviously more important at weaning or during gestation than after the growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…A control group of virgin female Wistar rats re ceived a diet containing 20% protein [Weinkove et al, 1977;Dixit and Kaung, 1985;Rodrigues et al, 1985), and a LP group received an isocaloric diet con taining 8% protein (table 1). The females were caged with males overnight and coitus was determined by inspection of vaginal smears; y 0 of gestation being the first day after coitus.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it was verified that the mucosa thickness presented gain deficit in protein malnourished animals (G3) when compared to eutrophic ones (G1) that were not supplemented with probiotics (p<0.05). On the other hand, the supplementation with probiotics (G4) provided a protective effect to the mucosa; this damage is generally observed in protein malnourishment (Viteri and Schneider 1974, Rodrigues et al 1985, Torrejais et al 1995, Natali et al 2000, Schoffen et al 2005, De Azevedo et al 2007, Hermes et al 2008. It is important to point out that the eutrophic animals were also supplemented with probiotics (G2) and presented thicknening of the mucosa when compared to G1, corroborating the studies that describe the proliferative effect induced by these microorganisms (Dock et al 2004a, AguilarNascimento et al 2006, Ng et al 2009).…”
Section: Resultsmentioning
confidence: 99%